2008
DOI: 10.3144/expresspolymlett.2008.90
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical significance of cellulose: A review

Abstract: Abstract. The amalgamation of polymer and pharmaceutical sciences led to the introduction of polymer in the design and development of drug delivery systems. Polymeric delivery systems are mainly intended to achieve controlled or sustained drug delivery. Polysaccharides fabricated into hydrophilic matrices remain popular biomaterials for controlled-release dosage forms and the most abundant naturally occurring biopolymer is cellulose; so hdroxypropylmethyl cellulose, hydroxypropyl cellulose, microcrystalline ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
191
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(202 citation statements)
references
References 131 publications
0
191
0
2
Order By: Relevance
“…This fact can be explained because HPMC is a forming polymer of hydrophilic matrix used to promote a slower release of the drug conditioned in the capsules. [20][21][22][23] The value found for the reference medicine (90.47%) resemble the values obtained for the capsules elaborated with HPMC, although this product is made from hard gelatin capsule. This may be related to the present excipients in the reference medicine (lactose, methylcellulose, stearic acid and magnesium stearate), which are different from the excipients used in the B formulation.…”
Section: Quality Control For Pharmaceutical Dosage Formmentioning
confidence: 69%
See 3 more Smart Citations
“…This fact can be explained because HPMC is a forming polymer of hydrophilic matrix used to promote a slower release of the drug conditioned in the capsules. [20][21][22][23] The value found for the reference medicine (90.47%) resemble the values obtained for the capsules elaborated with HPMC, although this product is made from hard gelatin capsule. This may be related to the present excipients in the reference medicine (lactose, methylcellulose, stearic acid and magnesium stearate), which are different from the excipients used in the B formulation.…”
Section: Quality Control For Pharmaceutical Dosage Formmentioning
confidence: 69%
“…The choice of hydrophilic polymer in the matrix formulation can provide an appropriate combination of the swelling mechanisms, dissolution or erosion and determine the release kinetics in vitro. 21 According to previous work, 22 the drug incorporation in hydrophilic matrix systems is the most used method to prolong drug release dosage forms for oral use. It was observed that with increasing amounts of HPMC in the formulations it is possible to get a reduced release of the drug, which can be evidenced in the dissolution tests.…”
Section: Quality Control For Pharmaceutical Dosage Formmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The main drawback to the use of cellulose for industrial applications is its insolubility in organic and aqueous solvents, with the supramolecular structures within and between polysaccharide strands being primarily responsible for insolubility. 3,[5][6][7] Chemical modification of the hydroxyl groups at C2, C3, and/ or C6 positions of cellulose has been developed to confer novel properties, including hydrophilic, antimicrobial, and thermoplastic character, where the degree of substitution (DS) and distribution of the substituents determines the modified cellulose structure and behavior. For cellulosebased materials, DS represents the average number of modified hydroxyl groups per AGU unit, where DS values can range from 0 to 3.…”
mentioning
confidence: 99%